Calcium Signaling in the Photodamaged Skin: In Vivo Experiments and Mathematical Modeling. Issue 1 (1st December 2021) - Donati, Viola; Peres, Chiara; Nardin, Chiara; Scavizzi, Ferdinando; Raspa, Marcello; Ciubotaru, Catalin D; Bortolozzi, Mario; Pedersen, Morten Gram; Mammano, Fabio
Abstract: The epidermis forms an essential barrier against a variety of insults. The overall goal of this study was to shed light not only on the effects of accidental epidermal injury, but also on the mechanisms that support laser skin resurfacing with intra-epidermal focal laser-induced photodamage, a widespread medical practice used to treat a range of skin conditions. To this end, we selectively photodamaged a single keratinocyte with intense, focused and pulsed laser radiation, triggering Ca 2+ waves in the epidermis of live anesthetized mice with ubiquitous expression of a genetically encoded Ca 2+ indicator. Waves expanded radially and rapidly, reaching up to eight orders of bystander cells that remained activated for tens of minutes, without displaying oscillations of the cytosolic free Ca 2+ concentration (${[ {{\rm{C}}{{\rm{a}}^{2 + }}} ]_c}$ ). By combining in vivo pharmacological dissection with mathematical modeling, we demonstrate that Ca 2+ wave propagation depended primarily on the release of ATP, a prime damage-associated molecular patterns (DAMPs), from the hit cell. Increments of the ${[ {{\rm{C}}{{\rm{a}}^{2 + }}} ]_c}$ in bystander cells were chiefly due to Ca 2+ release from the endoplasmic reticulum (ER), downstream of ATP binding to P2Y purinoceptors. ATP-dependent ATP release though connexin hemichannels (HCs) affected wave propagation at larger distances, where the extracellular ATP concentration was reduced by the combined effect of passive diffusion and hydrolysis due to the action of ectonucleotidases, whereas pannexin channels had no role. Bifurcation analysis suggests basal keratinocytes have too few P2Y receptors (P2YRs) and/or phospholipase C (PLC) to transduce elevated extracellular ATP levels into inositol trisphosphate (IP3 ) production rates sufficiently large to sustain ${[ {{\rm{C}}{{\rm{a}}^{2 + }}} ]_c}$ oscillations. Graphical Abstract: